Pengaruh Pemberian Pupuk Hayati Mikoriza Vesikular Arbuskular (VAM) dan Komposisi Media Tanam Terhadap Pertumbuhan Benih Kopi Arabika (Coffea arabica L.) - Abdillah, Fahmi; Setiawan, Andi; Warsito, Kabul (JURNAL AGROTEKNOLOGI UNIVERSITAS ANDALAS, 2025)
This research focused on assessing how the interaction between planting media composition and vesicular arbuscular mycorrhizal (VAM) biofertilizer influences the growth of Arabica coffee seedlings. The formulated hypothesis helped direct the study toward identifying the most favorable conditions for seedling development. The experimental design employed was a factorial randomized block design (RBD), comprising 16 different treatment combinations, each repeated twice. The first treatment variable (Factor P) involved different mixtures of topsoil, rice husk, and compost: P0 = 100% topsoil, P1 = 60% topsoil + 20% rice husk + 20% compost, P2 = 60% topsoil + 40% rice husk, and P3 = 60% topsoil + 40% compost. The second variable (Factor M) concerned the application of VAM biofertilizer in doses of 0 g (M0), 0.5 g (M1), 1 g (M2), and 1.5 g (M3). Statistical analysis showed that the interaction between media composition and VAM biofertilizer significantly influenced all growth indicators measured in the Arabica coffee seedlings.